2022
DOI: 10.5713/ab.21.0299
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated basil oil (Ocimum basilicum Linn.) enhances growth performance, intestinal morphology, and antioxidant capacity of broiler chickens in the tropics

Abstract: Title of the manuscript: Microencapsulated basil oil (Ocimum basilicum Linn.) enhances growth performance, intestinal morphology, and antioxidant capacity of broiler chickens in the tropical region ABSTRACT Objective: Microencapsulation is a technique to improveincrease stability, bioavailability, and controlled release of active ingredients at a target site. This experiment aimed to investigate the effects of microencapsulated basil oil (MBO) on growth performance, apparent ileal digestibility (AID), jejunal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…In this context, histomorphometric indices can be a more reliable indicator to assess intestinal health and function ( Awad et al, 2011 ; Al-Baadani et al, 2016 ). In the current study, we observed augmented villus height which corresponds to the previous reports ( Mohammadi et al, 2014 ; Mahdavi et al., 2014 ; Thuekeaw et al, 2022 ). Notwithstanding, Chowdhury et al (2018) and Jahejo et al (2019) reported that villus height remains unaffected while fed clove or tulsi.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this context, histomorphometric indices can be a more reliable indicator to assess intestinal health and function ( Awad et al, 2011 ; Al-Baadani et al, 2016 ). In the current study, we observed augmented villus height which corresponds to the previous reports ( Mohammadi et al, 2014 ; Mahdavi et al., 2014 ; Thuekeaw et al, 2022 ). Notwithstanding, Chowdhury et al (2018) and Jahejo et al (2019) reported that villus height remains unaffected while fed clove or tulsi.…”
Section: Discussionsupporting
confidence: 93%
“…Villus surface area was also increased in the experimental groups treated with low to medium concentrations of clove and tulsi. Thuekeaw et al (2022) also reported an increased villus surface area in broilers fed tulsi with their diet. Contrarily, Al-Mufarrej et al (2019) demonstrated that the inclusion of clove powder with feed decreases the villus surface area.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The positive effect of microencapsulated IgY on VH in this experiment may reflect the increased concentration of IgY reaching the small intestine [ 37 , 38 ]. Thuekeaw et al [ 39 ]. reported that adding 500 ppm of microencapsulated basil oil to their diets promoted VH:CD in the studied broilers compared with free basil oil [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thuekeaw et al [ 39 ]. reported that adding 500 ppm of microencapsulated basil oil to their diets promoted VH:CD in the studied broilers compared with free basil oil [ 39 ]. Therefore, microencapsulated IgY additions to livestock diets can improve the structure of small intestinal villi and promote the absorption and utilization of nutrients in the small intestine of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%